Предмет: Алгебра, автор: kotkate200027

Помогите пожалуйста!!!
(x-4)^2=(x-6)(x+6)+10
Надо решить!!!

Ответы

Автор ответа: Аноним
9

( х - 4 )² = ( х - 6 ) ( х + 6 ) + 10

х² - 8х + 16 = х² - 36 + 10

х² - 8х - х² = -36 + 10 - 16

-8х = -42

х = (-42) ÷ (-8)

х = 5,25.

Ответ : х = 5,25.

_____________________

Удачи))))


kotkate200027: Спасибо
Аноним: Не за что)
Автор ответа: ZLOYTIGROVSKIY
14

(x - 4) {}^{2}  = (x - 6) \times (x + 6) + 10 \\  \\ x {}^{2}  - 8x + 16 = x {}^{2}  - 36 + 10 \\  \\ x {}^{2}  - 8x - x {}^{2}  =  - 36 + 10 - 16 \\  \\  - 8 x =  - 42 \\  \\ x =  - 42 \div ( - 8) \\  \\ x = 5 \frac{1}{4}  = 5.25

~•~•~•ZLOY_TIGROVSKIY~•~•~•


kotkate200027: Спасибо
Похожие вопросы
Предмет: Алгебра, автор: xy1sdang
Предмет: Алгебра, автор: джонсуиин